Implementasi Integrasi Kurikulum 2013 dan Kurikulum Cambridge di SMP Al-Syukro Ciputat - Arik Nur Maudina; Hasanah (Qiro'ah : Jurnal Pendidikan Agama Islam, 2020)
This study tries to understand: (1) The purpose of implementing curriculum integration in Ciputat Al-Syukro Middle School; (2) Knowing the level of effectiveness of curriculum integration in Al-Syukro Ciputat Middle School on student achievement. (3) Knowing the supporting factors and inhibiting factors in implementing curriculum integration in Ciputat Al-Syukro Middle School. This study uses a qualitative method. Data collection techniques are done through observation, in-depth interviews, and observations. From the research conducted by the authors, the following results were obtained: (1) The aim of integrating the 2013 Curriculum and the Cambridge Curriculum at Ciputat Al-Syukro Middle School is to form students who have morality and competitive competitiveness in the era of globalization; (2) The results of the integration of the 2013 Curriculum and the Cambridge Curiulum are effective with graphical evidence of the results of final grades of students who are stable; (3) The strengths of curriculum integration in Al-Syukro Middle School are the ability to reason and English language skills that continue to increase according to the level. While the drawback is the lack of human resources in Ciputat Al-Syukro Middle School.